Baba Padmanji : vernacular Christianity in colonial India - Dandekar, Deepra (New York : Routledge Tylor and Francis Group, 2021)
"This book is a critical biography of Baba Padmanji (1831-1906), a firebrand native Christian missionary, ideologue, and litterateur from 19th-century Bombay Presidency. Though Padmanji was well-known, and a very influential figure among Christian converts, his contributions have received inadequate attention from the perspective of 'social reform' - an intellectual domain dominated by offshoots of the Brahmo Samaj movement, like the Prarthana Samaj in Bombay. This book constitutes an in-depth analysis of Padmanji's relationships with questions of reform, education, modernity, feminism, and religion, that had wide-ranging repercussions on the intellectual horizon of 19th-century India. It presents Padmanji's integrated writing persona and identity as a revolutionary pathfinder of his times who amalgamated and blended vernacular ideas of Christianity together with early feminism, modernity, and incipient nationalism. Drawing on a variety of primary and secondary sources, this unique book will be of great interest for area studies scholars (especially Maharashtra), and to researchers of modern India, engaged with the history of colonialism and missions, religion, global Christianity, South Asian intellectual history, and literature"--
Includes bibliographical references and index.
Keywords: Padmanji, Baba, -- 1831-1906.; Christian converts from Hinduism -- India -- Biography; Authors, Marathi -- 19th century -- Biography; Christianity -- India